New Early Cretaceous fossil from China documents a novel trophic specialization for Mesozoic birds - Hou, Lianhai (Naturwissenschaften, 2003)
We report on a new Mesozoic bird, Longirostravis hani, from the Early Cretaceous Jehol Biota of northeastern China. The new taxon has a long, slender rostrum and mandible, and a small number of rostralmost teeth. Postcranial characters such as a furcular ramus wider ventrally than dorsally, a centrally concave proximal margin of the humeral head, and a minor metacarpal that projects distally more than the major metacarpal, support the placement of Longirostravis within euenantiornithine Enantiornithes, the most diverse clade of Mesozoic birds. The morphology of the skull, however, suggests that Longirostravis had a probing feeding behavior, a specialization previously unknown for Enantiornithes. Indeed, this discovery provides the first evidence in support of the existence of such a foraging behavior among basal lineages of Mesozoic birds.